PERAN KARANG TARUNA DALAM PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT DI DESA LAU LEBAH KECAMATAN GUNUNG STEMBER KABUPATEN DAIRI - Simbolon, Deliyanti; Afrida, Fenny; Nasution, Lisa Elianti; Setyorini, Dian (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
This community service is focused on a workshop on the role of youth organizations in community development and empowerment in Lau Lebah Village, Gunung Sitember District, Dairi Regency. The determination of this workshop was motivated by the lack of involvement and participation of youth organizations in village progress. In an effort to increase village progress through the role of youth organizations, activities are needed that encourage increased involvement of youth organizations to create something new, whether in the form of ideas or real work. One of the activities held in Lau Lebah Village, Gunung Sitember District, Dairi Regency was holding a workshop on the role of youth organizations. Procurement of this workshop activity also shows that the Village aims to create youth youth activities in Village development with ADD provided by the village. The output target that will be produced from this PKM is in the form of knowledge transfer regarding the role of youth organizations in village development which is implemented in Lau Bee village. Apart from that, it is also hoped that this PKM activity will be able to develop the development of Lau Lebah Village towards future progress. The method of implementing the activity is pre-implementation, observation and interviews by the team, implementation of the activity, post-implementation after the socialization event is carried out. The result of this activity is an increase in the role of youth organizations in development and empowerment. From the workshop activities, youth organizations and village officials realized the important role of youth organizations in improving organizational management to increase village progress